Nenets Folklore in Russian: The Movement of Culture in Forms and Languages - Karina Lukin (Journal of Ethnology and Folkloristics)
In this methodological article the question of authenticity of folklore material is discussed. The article deals mainly with the research history of Nenets folklore studies and examines critically two of its paradigms, namely the so-called Finno-Ugric paradigm and the Soviet studies. It is argued that in these paradigms there existed biases that prevented the students to study certain kind of folklore material. The biases were related to the language and the form of the material: due to these biases folklore performed not in Nenets and not in forms defined traditional were left outside collections and research. Furthermore, it is shown that Russian speech and narratives embedded in speech are part of Nenets everyday communication and thus also material worth studying and collecting. Instead of the criticised paradigms the Nenets discourse is examined within the notions of communication centered studies that have gained attention since the 1980s.